Assessing the impact of tourism related development on the natural habitant using a Geographical Information System. - T. Mugwena (African Journal of Hospitality, Tourism and Leisure, 2019)
The growing attraction of tourism to protected areas comes with an increasing need to meet the demands of tourists; this includes building more infrastructure for accommodation and entertainment. Monitoring visitor impacts in protected areas requires a different approach to that taken to monitor impacts on the environment although some techniques could be the same. This study aims to develop a Current Environmental Character (CEC) for the Limpopo National Park (LNP) by using spatial analyses on data and information such as land use, tourist attractions, roads, and railways to identify the most impacted landscapes as well as those where visual and audible intrusion are absent, and which thus offer wilderness experience. The study successfully did CEC for the first time of the LNP in Mozambique. The classification used for the CEC was the ECHOS classification. The classification helped to identify how far the different zones of a CEC should be from an impact. The study found that multiplying the buffer values by two, increased impacted areas. This led to all the other zones of the CEC decreasing (natural undeveloped, wilderness edge and the wilderness area). Reducing the buffer values by half shrinks the impacted areas, increasing the other zones of the CEC. According to the results of the six CECs, it can be concluded that the most impacted areas are along the Limpopo River and near the Massingir dam. The pure wilderness of the park is found in the centre of the park and a small area of the wilderness situated north of the park. GIS can be used to study the impacts that tourism related infrastructure has on a park before any expansion is done.